2024
DOI: 10.1111/acel.14037
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic treatment alleviates doxorubicin‐induced chemobrain

Vivekananda Budamagunta,
Ashok Kumar,
Asha Rani
et al.

Abstract: Doxorubicin (Dox), a widely used treatment for cancer, can result in chemotherapy‐induced cognitive impairments (chemobrain). Chemobrain is associated with inflammation and oxidative stress similar to aging. As such, Dox treatment has also been used as a model of aging. However, it is unclear if Dox induces brain changes similar to that observed during aging since Dox does not readily enter the brain. Rather, the mechanism for chemobrain likely involves the induction of peripheral cellular senescence and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 153 publications
(203 reference statements)
0
4
0
Order By: Relevance
“…Impaired memory in males and females is linked to N-methyl-D-aspartate (NMDA) receptor hypofunction and alterations in synaptic plasticity processes that mediate episodic memory ( Kumar and Foster, 2013 ; Kumar et al, 2018 ; Barter et al, 2020 ; Budamagunta et al, 2023 ). In males, senolytic treatment increases hippocampal synaptic transmission, increasing NMDA receptor function and episodic memory ( Budamagunta et al, 2023 , 2024 ). Similarly, activation of membrane estrogen receptors in females increases NMDA receptor function and episodic memory ( Foster, 2005 ; Bean et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired memory in males and females is linked to N-methyl-D-aspartate (NMDA) receptor hypofunction and alterations in synaptic plasticity processes that mediate episodic memory ( Kumar and Foster, 2013 ; Kumar et al, 2018 ; Barter et al, 2020 ; Budamagunta et al, 2023 ). In males, senolytic treatment increases hippocampal synaptic transmission, increasing NMDA receptor function and episodic memory ( Budamagunta et al, 2023 , 2024 ). Similarly, activation of membrane estrogen receptors in females increases NMDA receptor function and episodic memory ( Foster, 2005 ; Bean et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The two treatments act on different mechanisms to promote apoptosis of senescent cells ( Chan et al, 2012 ; Zhu et al, 2016 ) and quercetin is an antioxidant ( Ishisaka et al, 2014 ). Importantly, dasatinib and quercetin, but not ABT-263, cross the blood brain barrier ( Porkka et al, 2008 ; Yamaguchi and Perkins, 2012 ; Ishisaka et al, 2014 ; Mehdipour et al, 2021 ; Budamagunta et al, 2023 , 2024 ). Both treatments improve cognition in males, emphasizing a link between cognitive decline and senescent cells in the periphery ( Budamagunta et al, 2023 , 2024 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vitro studies, low concentrations of doxorubicin have been found to induce aging in various cell types, including cardiomyocytes [ 25 ], human cardiac progenitor cells [ 26 ], vascular smooth muscle cells, human chondrocytes [ 27 ], fibroblasts [ 28 ], and several different types of human stem cells [ 29 , 30 ]. Similarly, in in vivo studies, doxorubicin has been validated to elevate senescence in C57BL/6 mice, result in brain aging in Fischer 344 rats and induce cellular senescence in murine ovaries [ 24 , 31 , 32 ]. Therefore, in the present study, doxorubicin was used as an aging inducer to induce stem cell senescence.…”
Section: Introductionmentioning
confidence: 99%